Source to sink analysis of weathering fluxes in Lake Baikal and its watershed based on riverine fluxes, elemental lake budgets, REE patterns, and radiogenic (Nd, Sr) and 10Be/9Be isotopes. (15th March 2022) - Suhrhoff, Tim Jesper; Rickli, Jörg; Christl, Marcus; Vologina, Elena G.; Pham, Viet; Belhadj, Moustafa; Sklyarov, Eugene V.; Jeandel, Catherine; Vance, Derek
Abstract: We present a detailed analysis of weathering fluxes at Lake Baikal, the largest lake in the world, using the major element, trace element and isotope geochemistry of major inflowing rivers, the lake itself, and its sediments. Our objective is to assess how lake records could be used to understand river-catchment-scale denudation and weathering processes. Total denudation rates at Lake Baikal, as obtained from meteoric 10 Be/ 9 Be, are an order of magnitude lower than the global average, at 16–35 t km −2 yr −1 . Chemical weathering rates obtained from the riverine dissolved load and discharge are, on the other hand, in the same range as global values, at 6–29 t km −2 yr −1 . Chemical weathering rates are higher in the north of the catchment than in the south, consistent with higher runoff in the north. In contrast, 10 Be/ 9 Be-derived denudation rates are higher in the south. We hypothesize that this pattern of variation may be due to the stabilizing effect of permafrost soils preventing erosion in the north. An inverse model shows that the Selenga River, Lake Baikal's major tributary, has a silicate weathering contribution to riverine dissolved cation fluxes of 42 mol%; this and other characteristics are representative of large rivers globally. Many trace elements have much lower concentrations in the lake than in inflowing rivers (Be (5%), Mn (3%), Fe (0.4%) and REE (1–2%)). We suggest, based on REE patterns and Mn, Fe-depth profiles in the lake, that this removal is the result of pH induced changes in dissolved-adsorbed partitioning at the river-lake interface, and the incorporation of trace elements into authigenic Fe-Mn (oxyhydr)oxide phases forming within the lake. Strontium is isotopically uniform within the lake, demonstrating that the whole lake mixes on a timescale shorter than its residence time (<330 years). Neodymium and Be, in contrast, show isotopic variability between the basins. While the Sr isotope budget of the lake is largely consistent with observed riverine Sr fluxes, an unradiogenic Nd source is needed to explain lake Nd isotope compositions, especially in the Northern Basin. This source appears to derive from old crustal rocks in this part of the catchment and could be hydrothermal, or small rivers that were not sampled here. Similarly, elevated 10 Be/ 9 Be ratios in the lake basins relative to the river input imply variable but significant atmospheric inputs of 10 Be into the lake. Overall, this study demonstrates that records of the paleo-chemistry of lakes, and Lake Baikal in particular, hold promise for understanding denudation and weathering on the continents, in ways that are more directly relatable to the environmental conditions of the catchment than is possible with marine records.